Microgravity, Bone Homeostasis, and Insulin-Like Growth Factor-1: A Review - John Kelly Smith (Recent Developments in Medicine and Medical Research Vol. 16, 2021)
ABSTRACT: Astronauts are at risk of losing 1.0-1.5% of their bone mass for every month they spend in space despite their adherence to high impact exercise training programs and diets high in nutrients, potassium, calcium, and vitamin D, all designed to preserve the skeletal system. This chapter reviews the basis of bone formation and resorption and details how exposure to microgravity or simulated microgravity affects the structure and function of osteoblasts, osteocytes, osteoclasts, and their mesenchymal and hematologic stem cell precursors. It details the critical roles that insulin-like growth factor-1 (IGF-1) and its receptor insulin-like growth factor-1 receptor (GF1-R) play in maintaining bone homeostasis and how exposure of bone cells to microgravity affects the function of these growth factors. Lastly, it discusses the potential of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), syncytin-A, sclerostin inhibitors, and recombinant IGF-1 (rIGF-1) as bone-saving treatments for astronauts in space and during colonization of the moon. IGF-1 and its receptor IGF1R play critical roles in all phases of bone formation, promoting both radial and linear bone growth.